Movement and olfactory signals: Sexually dimorphic antennae and female flightlessness in moths - Johnson, Tamara L.; Elgar, Mark A.; Symonds, Matthew R. E. (Frontiers in Ecology and Evolution, 2022)
Darwin argued a role for sexual selection in the evolution of male sensory structures, including insect antennae, the strength of which will depend upon the importance of early arrival at receptive females. There is remarkable variation in the nature and degree of sexual dimorphism in moth antennae, with males of some species having spectacular, feathery antennae. Although it is widely assumed that these elaborate structures provide greater sensitivity to chemical signals (sex pheromones), the factors underlying the interspecific diversity in male antennal structure and size are poorly understood. Because male antennal morphology may be affected by several female life–history traits, including flight ability, we conducted a phylogenetic comparative analysis to test how these traits are linked, using data from 93 species of moths across 11 superfamilies. Our results reveal that elaborate antennae in males have evolved more frequently in species where females are monandrous. Further, female loss of flight ability evolved more frequently in species where males have elaborate antennae. These results suggest that elaborate antennae have evolved in response to more intense male competition, arising from female monandry, and that the evolution of elaborate antennae in males has, in turn, shaped the evolution of female flightlessness.